Differences in Negotiated Facility Fees for Otolaryngology Procedures at Ambulatory Surgery Centers and Hospitals - Anika S. Walia; Roy Xiao; Daphne T. Hao; Vinay K. Rathi; Rosh K. V. Sethi; Stacey T. Gray (OTO Open)
Abstract While outpatient otolaryngology procedures have been increasingly performed at ambulatory surgery centers (ASCs), the cost differences compared to hospital outpatient departments (HOPDs) remain unclear. Utilizing newly available data collected from Turquoise Health's Rate Sense as required under the Transparency in Coverage rule, we assess, in this cross‐sectional analysis, the differences in negotiated facility fees between ASCs and HOPDs for 20 common otolaryngologic procedures. Analyzing data from 4613 ASCs and 2382 hospitals, we found significantly higher facility fees at HOPDs, with a median relative price difference of +146% (P < .0001). This may be explained by greater infrastructure costs and market power differences between facilities. Our findings suggest that further shifting outpatient otolaryngology procedures toward ASCs could yield substantial cost reductions across health care systems. Additional research is needed to ensure safe and cost‐effective patient selection for ASCs.